Penerapan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Hasil Belajar Siswa Kelas X Pada Materi Eksponen - Silvia Dwi Yanti; Devi Yusniati; Moh Syadidul Itqan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to determine the improvement of learning outcomes of tenth-grade students on the topic of exponents through the implementation of the Problem Based Learning (PBL) model. The PBL model is oriented toward solving contextual problems, enabling students to be more active, creative, and critical in discovering mathematical concepts.The research method used is classroom action research (CAR) following the Kemmis and McTaggart model, which was carried out in two cycles. Each cycle consists of the stages of planning, acting, observing, and reflecting. The subjects of the study were 28 tenth-grade students at MA Islamiyah Syafiiyah. The instruments used were learning outcome tests (post-tests for each cycle), and the Minimum Mastery Criteria (KKM) was set at 75. The action was considered successful if the percentage of classical mastery reached at least 75%. The results of the study showed a significant and consistent improvement in learning outcomes from the pre-cycle to Cycle II. In the Pre-Cycle, the class average score was only 48.93 with a very low classical mastery of 3.57% (only 1 student met the KKM of 75). After implementing the PBL model, the class average score in Cycle I increased to 64.82, with a classical mastery of 21.43% (6 students met the KKM). The most optimal improvement occurred in Cycle II, where the class average score rose to 75.18 and the classical mastery percentage successfully reached 75.18% (21 students met the KKM). This improvement indicates that PBL not only helps students understand the concept of exponents more deeply, but also enhances motivation and active engagement in the learning process. Thus, the implementation of the PBL model can improve students’ learning outcomes on exponent material and is worth applying as an effective alternative learning strategy